2014
DOI: 10.1093/aob/mct312
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional hybridization and reproductive barriers between two heterostylous primrose species in north-west Yunnan, China

Abstract: Hybridization is strongly asymmetric, with P. bulleyana the only possible mother and all detected hybrids being backcrosses in this direction. Partial ecological isolation and inhibition of heterospecific pollen, and possibly complete barriers to F1 formation on P. beesiana, may be enough to make F1 formation very rare in these species. Therefore, with no F1 detected, this hybrid zone may have a finite life span as successive generations become more similar to P. bulleyana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 79 publications
3
44
0
Order By: Relevance
“…Furthermore, the existence of F2 individuals indicated that the F1 hybrids were fertile, although they were not included in the sampling. Similar phenomena has been reported in heterostylous Primula (Ma et al ). The authors suggested that at least one F1 must have been present originally though it was not sampled.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the existence of F2 individuals indicated that the F1 hybrids were fertile, although they were not included in the sampling. Similar phenomena has been reported in heterostylous Primula (Ma et al ). The authors suggested that at least one F1 must have been present originally though it was not sampled.…”
Section: Discussionsupporting
confidence: 89%
“…The authors suggested that at least one F1 must have been present originally though it was not sampled. Therefore, hybrid zones can exist without F1s if the original F1 has died and no others have been formed (Arnold et al ; Cruzan and Arnold ; Chung et al ; Ma et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro embryo rescue is commonly used to bypass endosperm failure and allows the production of viable hybrid plants, supporting that the endosperm is a major cause of interspecific seed inviability [18,19]. Interestingly, several reports converge on the unidirectional effects of hybridization on seed phenotypes in genera such as Primula or Kalanchoe [19,20] and unidirectional gene flow between species has been commonly observed in natural conditions [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small sample size it is possible that this is an artifact, but it is also possible that certain other factors favor backcrossing to B. crispa in the wild. It is widely accepted that many types of pre- and post- zygotic barriers can act together to prevent hybridization and introgression [26–28]. Artificial pollination experiments only cover a small subset of these barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Seed viability tests were carried out using an X-ray image system (MX-20-DC12, Faxitron, USA, [28]). It should be noted that seed numbers were counted after seed dispersal, as fruit ripeness is difficult to assess in Buddleja .…”
Section: Methodsmentioning
confidence: 99%